2023
DOI: 10.1111/1753-0407.13386
|View full text |Cite
|
Sign up to set email alerts
|

Higher glucose fluctuation is associated with a higher risk of cardiovascular disease: Insights from pooled results among patients with diabetes

Abstract: Background The relationship between glucose fluctuation and the risk of cardiovascular disease (CVD) in patients with diabetes remains elusive. Glycated hemoglobin (HbA1c) variability is a key parameter of glucose fluctuation. Methods PubMed, Cochrane Library, Web of Science, and Embase were searched up to 1 July 2022. Studies reporting associations of HbA1c variability (HbA1c‐SD), coefficient of variation of HbA1c (HbA1c‐CV), and HbA1c variability score [HVS] with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Glycemic management in diabetic patients is now focused not only on effective glucose reduction, but also on how to avoid glucose fluctuations [ 1 ]. Our previous studies have shown that glucose fluctuations contribute to the development of many cardiovascular diseases [ 5 , 24 ]. More importantly, GF in type 1 diabetes can lead to increased myocardial fibrosis [ 6 ], but the pathophysiological mechanisms contributing to GF-induced myocardial fibrosis remain elusive, especially in type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycemic management in diabetic patients is now focused not only on effective glucose reduction, but also on how to avoid glucose fluctuations [ 1 ]. Our previous studies have shown that glucose fluctuations contribute to the development of many cardiovascular diseases [ 5 , 24 ]. More importantly, GF in type 1 diabetes can lead to increased myocardial fibrosis [ 6 ], but the pathophysiological mechanisms contributing to GF-induced myocardial fibrosis remain elusive, especially in type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose fluctuations, also known as glucose variability, are developing as an emerging indicator of glycemic control [ 1 , 2 ]. Previous studies have shown that a higher GF is independently associated with heart failure [ 3 ], arrhythmias [ 4 ], and cardiovascular events [ 5 ]. In type 1 diabetes, GF can lead to myocardial fibrosis [ 6 ]; however, there is currently limited understanding of whether GF can lead to myocardial fibrosis in type 2 diabetes and the mechanisms involved have not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…A recent analysis of 14 studies with 254,017 patients with diabetes revealed that the highest HbA1c variability is associated with increased risks of CVD. The CVD risk associated with HbA1c variability might be even higher among patients with T1D [12]. However, the role of short-term GV as a trigger of diabetic complications remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%